If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(8 + 3x) = 19 (8 * 7 + 3x * 7) = 19 (56 + 21x) = 19 Solving 56 + 21x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + 21x = 19 + -56 Combine like terms: 56 + -56 = 0 0 + 21x = 19 + -56 21x = 19 + -56 Combine like terms: 19 + -56 = -37 21x = -37 Divide each side by '21'. x = -1.761904762 Simplifying x = -1.761904762
| 8t+3(3t-2)=-5t-10 | | 5-2x/7=9/14 | | 5(3x-6)-3(x+1)-19x= | | 1/8+y=-7/16 | | -96=z+-83 | | 3x-3=21x+9 | | 8x+7=87 | | 4(-4y^5)= | | 3x=2x+17 | | x-1/7=13/14 | | (6x+1)(x-7)=0 | | 3z-5-z+3=0 | | 5/8x+7=-3/8x | | 14x-13/8-13x=10/8+3/8 | | -0.8x+0.5x-6=9 | | 6n^2=-8n-1 | | x-1/3=2x/5+1/15 | | x+x+15=x+45+x+40+x+25 | | 7z+10-4z=8+2z+10 | | y-13/23=-5/23 | | 6-1/2x=3/5 | | 2x-(x+2)-(x-2)=x-10 | | 2(n-3)-(4-5n)=6n | | f+-63=27 | | 5x^3-3x^2=2 | | (8x+7)(x-4)=0 | | -16(y+1)+5(4y-4)=3(y-3)+10 | | 4q+2=3q-2 | | 57.99-0.11d=58.54 | | 28x-4+6-15x-12x-20=-6 | | 7b+2b=63 | | 2x+15=3x+110 |